Binder‐Free Air Electrodes for Rechargeable Zinc‐Air Batteries: Recent Progress and Future Perspectives. Issue 4 (8th February 2021) - Yan, Xiaoxiao; Ha, Yuan; Wu, Renbing
Abstract: Designing an efficient air electrode is of great significance for the performance of rechargeable zinc (Zn)‐air batteries. However, the most widely used approach to fabricate an air electrode involves polymeric binders, which may increase the interface resistance and block electrocatalytic active sites, thus deteriorating the performance of the battery. Therefore, binder‐free air electrodes have attracted more and more research interests in recent years. This article provides a comprehensive overview of the latest advancements in designing and fabricating binder‐free air electrodes for electrically rechargeable Zn‐air batteries. Beginning with the fundamentals of Zn‐air batteries and recently reported bifunctional active catalysts, self‐supported air electrodes for liquid‐state and flexible solid‐state Zn‐air batteries are then discussed in detail. Finally, the conclusion and the challenges faced for binder‐free air electrodes in Zn‐air batteries are also highlighted. Abstract : The latest advancements in binder‐free air electrodes for electrically rechargeable zinc (Zn)‐air batteries are summarized. After a brief introduction of Zn‐air batteries with recently reported bifunctional active catalysts, self‐supported air electrodes for liquid‐state and flexible solid‐state Zn‐air batteries are discussed in detail. Finally, the challenges and opportunities for the binder‐free air electrodes are highlighted.